Effect of a waste management intervention program on knowledge, attitude, and practice (KAP) of nurses and housekeepers: a quasi-experimental study, Egypt - Eman Khashaba; Abdel Hady El-Gilany; Khadija Denewar (SpringerOpen, 2023)
Abstract Background Improper healthcare waste management practice is alarming in developing countries because resources are inadequate and waste management is often delegated to poorly educated and untrained laborers. This study aimed to compare the pre-KAP versus post-KAP towards the waste management program for nurses and housekeepers. In addition, it aimed to explore possible factors affecting the pre- and post-KAP in Mansoura Emergency University Hospital, Egypt. Subjects and methods One hundred thirty-three newly employed nurses, housekeepers, and those who need refreshment training as nominated by head nurses and link occupational health and safety nurses in the hospital were recruited for the study. The study's intervention included multiple training sessions using a PowerPoint presentation in Arabic with appropriate illustrations followed by an open discussion. An Arabic self-administered questionnaire containing demographic and occupational history, knowledge (27 questions), attitude (10 questions), and practice (9 questions) was used pre- and post-intervention. Results The overall KAP scores among the studied healthcare workers were significantly higher after the intervention. The pre- and post-knowledge scores were significantly different with respect to education, job description, and duration of employment (p < 0.05). The post-attitude scores were significantly different with respect to education and job description only (p < 0.05). The total pre-practice scores were significantly different with respect to education and job description (p < 0.05). However, the post-practice scores were significantly different with respect to sex, age, education, and job description (p < 0.05). Conclusion There was a significant improvement in the KAP scores post-intervention. The post-knowledge and attitude scores were significantly better in nurses and participants with a higher education. The post-practice score was significantly better for females, participants with an age ≥ 30 years, higher education, and nursing jobs. The combination of training and supervision was crucial for the success of waste management programs. Higher education levels are required for housekeepers to be capable of gaining better knowledge, follow rules, and be ready for any challenges in the future.